Combination of a Suzuki cross-coupling reaction using a water-soluble palladium catalyst with an asymmetric enzymatic reduction towards a one-pot process in aqueous medium at room temperature - Borchert, Sonja; Burda, Edyta; Schatz, Jürgen; Hummel, Werner; Gröger, Harald (Journal of Molecular Catalysis B-Enzymatic, 2012)
We report the combination of a palladium-catalyzed Suzuki cross-coupling reaction with an enzymatic reduction in a one-pot process in aqueous medium, in which both reaction steps are conducted at room temperature. By using a water-soluble palladium catalyst system, which is prepared from commercially available palladium chloride and TPPTS (tris(3-sulfonatophenyl)phosphine hydrate, sodium salt), the palladium-catalyzed step runs at room temperature in a mixture of isopropanol and water. After adjusting the pH value to pH 7, the resulting biaryl ketone is then directly reduced in situ via an enzymatic asymmetric reduction in the presence of an alcohol dehydrogenase (ADH), leading to the desired alcohol with up to >95% conversion (over two steps) and excellent enantioselectivities of >99% ee. Notably, both enantiomers of the desired alcohol are accessible depending on the source of applied ADH. © 2012 Elsevier B.V. All rights reserved.